On the particle size effect in expanded perlite aluminium syntactic foam. (5th February 2015) - Taherishargh, M.; Sulong, M.A.; Belova, I.V.; Murch, G.E.; Fiedler, T.
Highlights: Expanded perlite/Al syntactic foam was fabricated by infiltration process. The effects of cell size on the mechanical properties of foams were investigated. Smaller EP particles result in superior mechanical properties. Mechanical properties depend on microstructure and geometry of cell wall. Number of cell across the sample diameter has small effect on mechanical properties. Abstract: Packed beds of expanded perlite (EP) particles with three different size ranges (1–1.4, 2–2.8, and 4–5.6 mm) have been infiltrated with molten Al to produce EP/A356 Al syntactic foam. A T6 heat treatment was applied to the foams. The effects of EP particle size on microstructural, geometrical, and mechanical properties of the foams were investigated. The EP particle size determines the number of cells across the sample diameter (7–25). It also influences the microstructural characteristics of the cell-wall alloy and the homogeneity of the cell-wall geometry. Enhanced microstructural characteristics and a greater geometrical homogeneity of the cell-wall in the case of smaller EP particles result in superior mechanical properties. The compressive deformation becomes more uniform by decreasing the EP particle size resulting in smoother and steeper stress–strain curves. As a result, these foams exhibit higher plateau stresses and improved energy absorption. The number of cells across the sample diameter does not have a significant effect on the mechanical properties of the samples considered.